Generation-wise performance evaluation of Ghoongroo pig: An effort to improve the productivity - BANIK, SANTANU; KUMAR, SATISH; DAS, PRANAB JYOTI; BARMAN, KESHAB; THOMAS, R; ISLAM, R; KUMAR, SUNIL; GUPTA, V K (The Indian Journal of Animal Sciences, 2024)
Ghoongroo pig is the first recognized pig breed in India from the North Bengal and adjoining districts of Assam. This breed has been evolved through continuous breeding and selection within its native breeding tract. The present investigation aimed to evaluate the genetic performance of Ghoongroo pigs across generations, utilizing data collected over a 13-year period (2008-2021) from the Nucleus Pig Breeding Farm at the ICAR-National Research Centre on Pig in Guwahati, Assam. The analysis of productive, reproductive and carcass traits revealed continuous improvements in litter size, litter weight, weaning weight and other traits over successive generations due to selective breeding. The study highlighted the consistent genetic progress achieved through selective breeding within the Ghoongroo pig breed. The scientifically managed nucleus herd of Ghoongroo pigs at the research institute serves as a valuable repository for preserving the breed’s genetic resources and acts as a conservation unit for this unique indigenous breed.